Influence of floral and aromatic plant materialson incense stick preparation and properties - Dhakad, G S; Kashyap, B; Dhiman, S R; Sharma, P; Bhardwaj, S K; Pathania, S; Kumar, A (Journal of Horticultural Sciences, 2025)
In India, floral waste is disposed of in rivers and water bodies annually, leading to significant pollution. However, this waste can be substantially reduced if utilized effectively. One promising application is the use of floral waste in the production of value-added products. This study specifically explores the potential of repurposing waste to manufacture incense sticks. Two experiments were conducted to identify the optimal combination of flower petal powder and adhesives for making incense sticks. In experiment 1, sixteen different treatments of flower petal powder and adhesive combinations were tested. The treatment consisted of rose petal powder 42.5% and marigold petal powder 42.5% mixed with 15% Jigat powder as adhesive was found to be the most effective, followed by a combination of marigold petal powder 85% and 15% Jigat powder as adhesive. In experiment 2, the two best treatments from experiment 1 were mixed with aromatic plant powder in various proportions to create naturally fragrant incense sticks. The mosquito repellent activity and olfactory evaluation of these incense sticks were assessed. It was observed that the combination of rose petals, marigold petals, Jigat powder, and 30% lemongrass powder yielded the best results.
Keywords: flowers; fragrance; incense sticks; insect repellent; waste recycling